Synthesis, Antimicrobial Activity and Semi-conducting Properties of Novel 2-(4-Chloro-1-Naphtyloxy)-2-Oxoethyl Methacrylate with 2-(Diethylamino)Ethyl Methacrylate Copolymers - Soykan, Cengiz; Yakuphanoğlu, Fahrettin; Sahin, Muradiye (Taylor & Francis Inc, 2013)
The free-radical initiated copolymerization of 2-(4-chloro-1-naphtyloxy)-2-oxoethyl methacrylate (ClNOEMA) with 2-(diethylamino) ethyl methacrylate (DEAEMA) was carried out in 1,4-dioxane solution at 70 +/- 1 degrees C using 2,2-azobisisobutyronitrile (AIBN) as an initiator with different monomer-to-monomer ratios (ranging from 0.15 to 0.85) in the feed. The copolymer composition obtained by elemental analysis led to the determination of reactivity ratios employing Fineman-Ross (F-R) and Kelen-Tudos (KT) linearization methods. These parameters were also estimated using a non-linear computational fitting procedure, known as reactivity ratios error in variable model (RREVM). The prepared homo and copolymers were tested for their antimicrobial activity against bacteria and yeast. These copolymers have been converted into novel salts by reaction with the iodemethane (CH3I). The copolymers and the corresponding salts have been characterized fully by a range of spectroscopic analysis techniques. The electrical conductivity dependence of temperature of the polymers were measured and the polymers exhibit the semi-conducting behavior, confirming that the electrical conductivity increases with increasing temperature. The poly(CINOEMA-co-DEAEMA) polymer doped by CH3I for 15min shows the highest conductivity. The optical band gap, activation energy and room temperature conductivity values of these polymers were obtained. These electronic parameters suggest that the poly(CINOEMA-co-DEAEMA)s doped by CH3I for 15min is an organic semiconductor with the thermally activated conduction mechanism.
Keywords: Copolymerization; monomer reactivity ratio; 2-(4-chloro-1-naphtyloxy)-2-oxoethyl methacrylate; antimicrobial activity; semi-conducting properties